883 Clinical Case Report: Recurrent Non-Tuberculous Psoas Abscess with Associated Discitis. (19th August 2022) - Palepa, A; Morrison, TEM; Suresh, S; Arulampalam, T
Abstract: Introduction: Following the discovery of modern anti-tuberculosis treatments, psoas abscesses secondary to Pott's disease of the spine rarely occur in developed countries. We present a case of a recurrent non-tuberculous psoas abscess communicating with the spine and pleural cavity, presenting as an abdominal mass. Case: A 72-year-old man presented with a left upper quadrant mass, pain, abdominal distension and raised inflammatory markers. Cross-sectional imaging with CT and MRI revealed a large left-sided psoas abscess with a pleural effusion tracking to the retroperitoneum and associated recurrent discitis. The patient was commenced on intra-venous antibiotics and the collection was accessed via a radiologically placed drain to the retroperitoneum. Discussion: Spinal infections may present with a lump below the inguinal ligament due to pus tracking down the psoas tendon sheath. Irritation of the psoas muscle may also present with pain on hip extension due to muscular spasm. The most common causative agent of primary psoas abscesses is Staphylococcus Aureus. Discitis is more common in men and shows a bimodal age distribution in presentation, predominantly affecting children and then those in the 6 th -7 th decade of life. Learning points: Retroperitoneal disease should be considered in a patient who presents with an abdominal mass. In patients who present with a psoas abscess or an empyema communicating with the retroperitoneum, a spinal source should be considered. Crohn's disease is a common cause of secondary psoas abscesses and should also be considered. Cultures for mycobacteria should be obtained to exclude Tuberculosis as an underlying cause.